Estimation of Multivariate-GARCH Models to Stock Return an Islamic Banks in Indonesia and Malaysia - Zaini Ibrahim; Anita Anita; Siti Marfuah; Nurul Fitriani (Islamiconomic : Jurnal Ekonomi Islam, 2025)
This research aims to forecast Islamic banking stock returns and compare the stock performance of Islamic banks in Indonesia and Malaysia. This research uses the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) method in estimating stock volatility with variance based on market models, known as the Conditional-Capital Pricing Asset Model (C-CAPM). The sample selection technique used a purposive sampling method, and a sample of three commercial Islamic shares in Indonesia and four shares of Bank Islam Malaysia were obtained. The research results prove that Islamic Commercial Bank shares on the Indonesian and Malaysian Stock Exchanges are efficient shares so they are recommended to own, with a ranking based on actual return calculations in Indonesia, namely: 37.7% (BRIS); 35.5% (PNBS); 5.70% (BTPS); and in Malaysia. as follows: 35.7% (KFH); 13.6% (AFIN); 1.70% (RAJHI); 1.0% (CIMB). The Welch F-test with the C-CAPM model proves no difference between the stock returns of Islamic banks in Indonesia and Malaysia.